Improving the performance of baitul maal wat tamwil (BMT) employees: Do the principles of good corporate governance (GCG) matter? - Nugraheni, Peni; Nasiroh, Candra Dewi (Journal of Accounting and Investment, 2023)
Research aims: The role of human resources in Baitul Maal wat Tamwil (BMT) is vital as it is the main driver of all company activities in achieving its goals. This study, therefore, aims to examine the influence of corporate governance (CG) principles on employee performance in BMT. Design/Methodology/Approach: The object of this study was BMTs in Yogyakarta Province, with the respondents being BMT employees. The data collection technique employed a questionnaire measured by five Likert scales. The data in this study were then processed using the multiple linear regression method. Research findings: The study uncovered that all CG principles, i.e., transparency, accountability, responsibility, independence, and fairness, positively influenced employee performance. Theoretical contribution/Originality: This study contributes to the development of BMT management in Indonesia to start or improve the implementation of corporate governance since it positively impacts employee performance. Practitioner/Policy implication: BMT has challenges related to human resource competence. The organization (BMT) can evaluate the implementation of GCG in its operational activities because it can affect employee performance. Research limitation/Implication: The study only took samples from Yogyakarta Province. The physical distribution of questionnaires also limited the number of samples that could be collected.